ANALYSIS OF LOCAL RESOURCE POTENTIAL IN INDUSTRIAL AREA DEVELOPMENT IN SELAYAR ISLANDS REGENCY - Baharuddin, Baharuddin; Maulana, Zulkifli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Selayar Islands Regency has abundant natural resource potential, especially in the agriculture, livestock, plantation, fisheries, and forestry sectors. However, its utilization is still limited to local needs and has not been developed optimally as a superior commodity with high economic value. This study aims to identify the base sectors that have the potential to be developed in the industrial area and to assess the economic feasibility of the Selayar industrial area project. The method used was the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analysis to determine the base and prospective sectors. The results of the study indicated that the leading sectors that could be developed include industries using coconut, tangerines, and fisheries as raw materials. LQ values > 1 were found in commodities such as free-range chickens, goats, coconuts, large pelagic fish, and reef fish. These findings recommend the development of industrial areas based on local potential as a strategy to accelerate economic growth in Selayar Islands Regency. Keywords: Industrial Area, Location Quotient, Local Resources, Selayar Islands Regency.